EFFECTIVENESS OF SHOULDER GLIDES WITH ROTATION IN ADHESIVE CAPSULITIS: A RANDOMIZED CONTROLLED TRIAL (Journal of Medical & Health Sciences Review, 2025)
Background: Adhesive capsulitis (frozen shoulder) is a common condition characterized by pain and restricted shoulder range of motion (ROM), significantly affecting functional independence. While several treatments exist, evidence remains limited regarding the efficacy of shoulder glides with rotation as a therapeutic intervention.Objective: To evaluate the effectiveness of shoulder glides with rotation in reducing pain and improving shoulder ROM and function in individuals with primary adhesive capsulitis.Methods: A single-masked, parallel-group randomized controlled trial was conducted over 8 weeks at two rehabilitation centers in Peshawar, Pakistan. Sixty participants aged 40–65 years with idiopathic adhesive capsulitis were randomized into two groups: an intervention group (shoulder glides with rotation and home exercise) and a control group (conventional physiotherapy). Both groups received treatment three times per week for 6 weeks. The primary outcome was the Shoulder Pain and Disability Index (SPADI); secondary outcomes included a range of motion (ROM) in flexion, abduction, and external rotation, a Visual Analog Scale (VAS) for pain, and the Functional External Rotation Reach Test (FERRT). Assessments were conducted at baseline, week 3, week 6, and week 8. Data were analyzed using repeated-measures ANOVA and intention-to-treat analysis.Results: Fifty-seven participants completed the study (SGR = 29, Control = 28). The intervention group showed significantly greater improvements in SPADI scores (Week 6: 31.4 ± 6.8 vs. 45.7 ± 7.2; p < 0.001), ROM (flexion gain: +41.5°, abduction: +41.4°, external rotation: +30.2°; all p < 0.001), and VAS for pain at rest (–4.3) and during activity (–4.5) compared to controls. Functional reach (FERRT) improved significantly in the intervention group (+13.2 cm vs. +6.1 cm; p < 0.001). Effect sizes for all key outcomes were large (Cohen’s d > 1.0).Conclusion: Shoulder glides with rotation significantly improved pain, ROM, and functional performance in patients with adhesive capsulitis compared to conventional physiotherapy. These findings support the integration of rotational joint mobilization into evidence-based rehabilitation protocols for frozen shoulders.